Extraction efficiency of different microplastic polymers from deep-sea sediments and their quantitative relevance - Canensi, Sara; Barucca, Gianni; Corinaldesi, Cinzia (Frontiers in Marine Science, 2022)
An increasing number of methods for extracting microplastic particles from marine sediments have been published but without evaluating the extraction efficiency. Furthermore, while most of the procedures developed have been applied to sandy sediments from shallow water habitats, specific and standardized procedures for deep-water sediments (> 200 meters deep) are limited. In this study, we describe a specific protocol for extracting microplastics (2- 1000 µm) from deep-sea sediments and for quantifying and identifying them. We also assessed its extraction efficiency, which resulted in a high recovery (on average ca. 60%, and up to 80%) particularly, for polyethylene, polypropylene, and polystyrene. This method allows the extraction of even the smallest fraction of microplastics (down to 2 µm) and can be applied to all muddy sediments and adapted for the recovery of nano-plastics, which are expected to have the most severe effects on marine biodiversity and ecosystem functioning and ultimately also have implications for human health.